Periodontitis, erectile dysfunction, reproductive hormones, and semen quality: A systematic review. (2nd January 2021) - Lecaplain, Bastien; Badran, Zahi; Soueidan, Assem; Prud'homme, Tony; Gaudin, Alexis
Abstract: Background: There is increasing evidence that periodontitis may affect male sexual health (MSH) (erectile function, production of sex hormones, and semen quality). However, a limited number of clinical studies demonstrate the association between MSH and periodontitis. Objectives: The aim of this study was to explore the relationship between periodontitis and MSF. Materials and methods: A comprehensive systematic review of the published literature in MEDLINE, PubMed, Scopus, Cochrane, EMBASE, and Web of Science databases from the earliest available online indexing year until October 2020 was performed, in accordance with the PRISMA guidelines. Keywords related to periodontitis were combined with words describing MSH. Result: A total of 19 studies were included and discussed in the systematic review. The number of study participants ranged from 53 to 197, 136 individuals, aged between 18 and 95 years (mean age, 41.2 years). Six studies did not report the age of the participants. Out of nine studies, eight found a significant association between erectile dysfunction (ED) and periodontitis. Only three studies evaluated the association between sex hormone levels and periodontitis, and two of these studies showed that patients with periodontitis are expected to exhibit higher levels of testosterone. Finally, out of five studies, two demonstrated a significant association between semen quality and periodontitis. Discussion: The findings in this review were limited by the quality and the few available studies. Results from the observational studies might have been affected by recall bias and confounded by cofactors. Conclusion: The results of this systematic review revealed a significant association between periodontitis and ED, although the responsible mechanisms remain unclear. The potential associations between sex hormone levels, semen quality, and periodontitis are yet to be demonstrated. In order to improve patient management, dentists and physicians need to be aware of the association between male sexual health problems and periodontitis.